Enhancement of Event-Related Desynchronization in Motor Imagery Based on Transcranial Electrical Stimulation - Xie, Jiaxin; Peng, Maoqin; Lu, Jingqing; Xiao, Chao; Zong, Xin; Wang, Manqing; Gao, Dongrui; Qin, Yun; Liu, Tiejun (Frontiers in Human Neuroscience, 2021)
Due to the individual differences controlling brain-computer interfaces (BCIs), the applicability and accuracy of BCIs based on motor imagery (MI-BCIs) are limited. To improve the performance of BCIs, this paper examined the effect of transcranial electrical stimulation (tES) on the brain activity during motor imagery (MI). This paper designed an experimental paradigm that combines tES and MI, and examined the effects of tES based on the measurements of electroencephalogram (EEG) features in MI processing, including the power spectral density (PSD) and dynamic event-related desynchronization (ERD). Finally, we investigated the effect of tES on the accuracy of MI classification using linear discriminant analysis (LDA). The results showed that the ERD of the μ and β rhythms in the left-hand MI task were enhanced after electrical stimulation with a significant effect in the tDCS group. The average classification accuracy of the transcranial alternating current stimulation (tACS) group and transcranial direct current stimulation (tDCS) group (88.19% and 89.93% respectively) were improved significantly compared to the pre- and pseudostimulation groups. These findings indicated that tES can improve the performance and applicability of BCI and that tDCS was a potential approach in regulating brain activity and enhancing valid features during noninvasive MI-BCI processing.